Applied electric field on the reaction between submerged entry nozzle and alloy in the steel. Issue 16 (15th August 2021) - Tian, Chen; Yuan, Lei; Li, Yan; Jia, Danbin; Wen, Tianpeng; Liu, Guoqi; Yu, Jingkun; Li, Hongxia
Abstract: In this study, the reactivity between nozzle and submerged entry nozzle and alloy elements in the steel (Al and Ce) under different electric field conditions was investigated. The results show that the decarburization of the nozzle is an important factor affecting the clogging behavior and steel quality. The external electric field directly affects and changes the decarburization, clogging, and reaction behavior between the nozzle and alloy in the steel. If the chemical reaction force between alloys and the nozzle is greater than the applied electric field force in actuality, the clogging will also occur on the submerged entry nozzle. In the future, this new method of controlling and changing the interfacial electric fields can be used to solve the problem of decarburization and clogging of the submerged entry nozzle.